THE THEORETICAL FOUNDATIONS OF THE STATE’S ROLE IN ECONOMIC PROCESSES AND THE ATTRACTION OF FOREIGN INVESTMENTS - Mamatqulov Bekzod Akmalovich (Modern American Journals, 2025)
In this study, the theoretical foundations of the state’s role in economic processes and the attraction of foreign investments are analyzed. The state is regarded as the main institution that regulates and directs the economy toward sustainable growth. Through production, fiscal, tax, and foreign trade policies, it enhances the competitiveness of the national economy, creates a favorable environment for investments, and ensures social stability. At the same time, the process of attracting foreign investments is substantiated as a crucial factor for economic growth, technological modernization, and deepening international integration. The research scientifically highlights the strategic directions of economic policy, mechanisms for shaping the investment environment, and the theoretical and practical functions of the state.
Keywords: State economic policy, economic processes, state regulation, foreign investments, investment environment, economic stability, national economy, market mechanisms, international integration.